SUMMARIZING SHORT STORY TO IMPROVE ENGLISH VOCABULARY MASTERY IN SMP NEGERI 2 BAUBAU - Astriana Astriana; Waode Hanafiah; Sanaria Maneba (English Education Journal, 2020)
Problem in this research was whether summarizing short story improved students’ vocabulary mastery in SMP Negeri 2 Baubau. This research aimed at improving students’ vocabulary mastery by summarizing short story in eight grade of SMP Negeri 2 Baubau. This research applied quasi experimental design with two groups, control and experimental class. The population of the research were 330 students. The sample of this research consisted of 62 students selected by using random sampling technique. The instrument used in this research was test. Research outcome showed that the mean score of pre-test from experimental class was 54.35, while in post-test 87.74. Meanwhile, the mean score of the pre-test result from control class was 52.77 and in the post-test 75.81. From hypothesis test result by using t-test, it obtained t-count was -.12.285 and the significant value 0.000 <0.05. So that, it can be concluded that Ha was accepted and H0 was rejected. Therefore, the summarizing short story to improve English vocabulary mastery in SMP Negeri 2 Baubau was effective.